Alkaline anion exchange membranes with imidazolium-terminated flexible side-chain cross-linked topological structure based on ROMP-type norbornene copolymers. (8th May 2020) - He, Xiaohui; Cheng, Changwen; Huang, Shengmei; Zhang, Feng; Duan, Yapeng; Zhu, Chuanyi; Guo, Yan; Wang, Kai; Chen, Defu
Abstract: We incorporate epoxy group functionalized side chain and imidazolium-terminated flexible side chain to norbornene copolymer backbone result in forming a space cross-linked topological structure for alkaline anion exchange membrane (AAEM). The introduction of epoxy groups to the copolymer backbone gives it some special properties, such as good solubility in ordinary organic solvent and the formation of self-cross-linked structure under alkaline environment without additional cross-linker or initiator. The as-prepared copolymers show excellent thermal stability (Td > 320 °C). The self-assembly of hydrophilic flexible side chains and hydrophobic polymer backbone result in well-defined micro-phase separation. The hydroxide conductivity of AAEMs as high as 90 mS cm −1 at 80 °C and after 10 days in 2 M NaOH aqueous at 60 °C the hydroxide conductivities of membranes only decreased by 25%. A peak power density of 118.4 mW cm −2  at a current density is 253.1 mA cm −2 is demonstrated. Graphical abstract: Image 1 Highlights: Epoxy group and imidazolium group with flexible side chain were incorporated into norbornene-based copolymer for AAEMs. The AAEMs show a well-defined microscopic phase separation structure. The AAEMs formed self-cross-linked topological structure under high pH conditions. The hydroxide conductivity was measured as high as 90.0 mS cm −1  at 80 °C..